ANALYSIS OF THE EFFECTIVENESS OF RETRIBUTION FOR CLEANING SERVICES AT THE ENVIRONMENTAL SERVICE OF BENGKALIS REGENCY - Dwi Aini; Husni Mubarak (Finance and Investment Program, School of Business and Management - Petra Christian University, 2021)
Garbage/cleaning service levies are for waste/cleaning services provided or managed by the local government for individuals or entities. This study aims to determine the mechanism of retribution collection, the effectiveness of retribution for Regional Original Income (PAD), and the obstacles encountered when collecting retribution. This research was conducted at the Bengkalis Regency Environmental Service. The research object is a report on the realization of waste/cleaning retribution receipts from 2018 to 2020. This type of research uses a qualitative descriptive approach. Based on the study results, in the process of collecting retribution for the garbage/cleaning service, those who have paid the levy are given evidence of a Certificate of Regional Retribution (SKRD) in the form of a ticket from the retribution collector. At the Bengkalis Regency Environmental Service, the SKRD is divided into two types, namely daily and monthly. The sub-districts that have increased yearly are Bengkalis, Bantan, and Siak Kecil sub-districts within 3 to three years. Meanwhile, other sub-districts experienced instability in their retribution receipts. In 2018 the waste/cleaning retribution 2018 got a percentage of 89%, which cannot be said to be very effective because it is still below 100% of the target achievement level. In 2019, waste/cleaning service levy received 116%, with a very effective statement. In 2020, the effectiveness of receiving retribution for waste/cleaning services in all sub-districts was at a very effective point in increasing local revenue, with an average effectiveness value of 145%. Constraints in collecting user fees are that the user does not know about the existence of regulations regarding collecting payments. There are no sanctions for mandatory fees if he does not pay the user fees, the lack of supervision, the number of retribution collectors, and limited facilities and infrastructure.